Accountability of Budget Users and Proxy Budget users on the Emergence of State Losses in the Procurement of Government Goods/Services - Rustanto (Universitas Airlangga, 2022)
Many criminal acts of corruption originate from the procurement of goods/services which turns out to not make the application of the article on corruption crimes to matters relating to state losses or the application of corruption crimes to KPA and PA actions important to get attention, because many parties are certainly familiar with the character of law enforcement for criminal acts of corruption, which are always linked with administrative errors. Based on this background, this research raises the title: